2000
DOI: 10.1016/s0375-9601(00)00561-2
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic-field-controlled twin boundaries motion and giant magneto-mechanical effects in Ni–Mn–Ga shape memory alloy

Abstract: This report represents some new experimental results and the quantitative model describing large magneto-strain effect and main mechanical and magnetic properties observed in several ferromagnetic shape-memory alloys. The model application to giant magneto-strain effect recently found in some non-stoichiometric Ni-Mn-Ga alloys is discussed.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
190
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 287 publications
(195 citation statements)
references
References 21 publications
(48 reference statements)
5
190
0
Order By: Relevance
“…Several studies on Ni-Mn-Ga alloys have addressed martensite transformation and correlation between magnetism and crystallographic structures [6][7][8][9][10][11][12][13][14][15][16][17][18]. Ma et al [7] studied the crystallography of Ni 50+x Mn 25 Ga 25-x alloys (x = 2-11) by powder X-ray diffraction and optical microspectroscopy.…”
Section: Outlinementioning
confidence: 99%
See 2 more Smart Citations
“…Several studies on Ni-Mn-Ga alloys have addressed martensite transformation and correlation between magnetism and crystallographic structures [6][7][8][9][10][11][12][13][14][15][16][17][18]. Ma et al [7] studied the crystallography of Ni 50+x Mn 25 Ga 25-x alloys (x = 2-11) by powder X-ray diffraction and optical microspectroscopy.…”
Section: Outlinementioning
confidence: 99%
“…The typical width of a variant is about 1 μm, by means of the TEM image of Ni 54 Mn 25 Ga 21 , which is shown in [7], and the strict twin structure of the microstructure is beneficial to the thermoelasticity of its martensitic transformation. A few studies discussed the interaction between magnetism and crystallographic rearrangements [1,8,9,17,18]. The memory strain, which means the second thermal cycle and the relative elongation obtained before the pre-deformation, was observed in single crystal Ni 2 MnGa and polycrystal Ni 53.6 Mn 27.1 Ga 19.3 [10].…”
Section: Outlinementioning
confidence: 99%
See 1 more Smart Citation
“…Wang et al calculated the energy consumed for the martensite/parent interfacial motion during the martensitic transformation using a boundary friction phenomenological theory 7) . Likhacheö et al suggested that the magnetic driving force applied to twin boundaries is equal to a difference in magnetization free energies between the different twin variants of martensite and this kind of force will achieve its maximal value 0.13 MN/m 2 in a magnetic eld based on the experimental results and the theoretical model 8) . The martensitic structure in the Ni-Mn-Ga alloy has been studied intensively and was found to be composition-, stressand temperature-dependence [9][10][11][12][13] .…”
Section: Introductionmentioning
confidence: 99%
“…Several studies on Ni-Mn-Ga alloys address the martensite transition and correlation between magnetism and crystallographic structures [6][7][8][9][10][11][12][13][14][15][16][17][18]. Ma et al studied the crystallography of Ni50+xMn25Ga25-x alloys (x = 2-11) by powder X-ray diffraction and optical microspectroscopy [7].…”
Section: Introductionmentioning
confidence: 99%